Where and How Does Fitting in Matter? Examining New Students' Perceived Fit With Their University, Instructors, and Classmates. (May 2020) - Knapp, Joshua R.; Masterson, Suzanne S.; Kedharnath, Uma
Researchers routinely find that individuals and organizations are better off when the personal characteristics of members fit with contextual organizational characteristics. Typically, this kind of research examines employees and the work environment. However, the dynamics of fit can be applied broadly, and some researchers have found fit-related theory to be a useful tool for examining students' relationships with their universities. We build on this body of work by using new students' perceptions of needs-based and values-based fit with their university, instructors, and classmates to predict both intention to recommend and turnover intention. For the purposes of recruitment and retention, results emphasize the importance of needs-based fit with the university and with classmates.